Correlation between vibrational modes, crystal structures, and dielectric properties of (1 − x)Ba(Mg1/3Ta2/3)O3–xBa(Co1/3Nb2/3)O3 ceramics. Issue 23 (6th August 2018) - Li, Jianzhu; Fang, Liang; Zhao, Guoxiang; Xing, Chao; Qiao, Hengyang; Chen, Huiling; Zeming, Qi; Wang, Qing; Shi, Feng
Abstract: Abstract : (1 − x )Ba(Mg1/3 Ta2/3 )O3 – x Ba(Co1/3 Nb2/3 )O3 (BMT–BCN, x = 0.0, 0.20, 0.25, 0.30, 0.40) ceramics were prepared using the traditional solid-state reaction method. X-ray diffraction patterns have shown that the intensities of (001) and (100) super-lattices decrease with the increase in the BCN content. Seven main Raman vibrational modes are observed, assigned, and illustrated, in particular. Raman shifts of Eg (O) modes and the FWHM values of F2g (O)/A1g (O) modes have close relationship with the dielectric properties. The calculated values by the four-parameter semiquantum model based on IR reflectivity match well with the measured data (@3.8 GHz), which means that most of dielectric contribution to the system may be ascribed to the absorption of structural phononic oscillations at the infrared region, and the contribution from the scattering of the defective phonons is small. The contributions of each vibrational mode on the dielectric responses were investigated in detail, indicating that the low-frequency modes (A2u (1) and Eu (1) ) have a decisive role to the dielectric properties.